Efficacy of osmotic laxative polyethylene glycol 4000 in treatment of constipation in pediatrics - S. I. Erdes; B. O. Matsukatova; S. A. Revyakina; Ye. V. Casanave (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. To evaluate the dynamics of clinical symptoms of constipation at children and parameters of peripheral electrogastroenterography (PEGEG) on treatment with osmotic laxative polyethylene glycol 4000 (PEGs).Material and methods. For treatment of constipation in 15 children aged 5 to 17 years (average – 9,9±3,9 year) 14-day's course of intake of osmotic laxative PEG (Forlax®, «Beaufour Ipsen Pharma», France) was prescribed. The drug was prescribed under following mode: to children under 8 years of age - 1 sachet (4 g) bid (8 g/day), over 8 years – 1 sachet (10 g) 2 times day (20 g/day) for 14 days. With the help of specifically designed original questionnaire dynamics of clinical symptoms of constipation, and changes of scores of electrical activity of various regions of gastro-intestinal tract (GIT) by PEGEG was estimated. Results were processed by computer programs Microsoft Excel and Statistika 7.0 software.Results. Complaints prior to the treatment onset included constipation (93%), difficulty of defecation (93%) and straining at defecation (87%). All children complained of hard stool. Complaints of long time spent in lavatory (67%) and «scybalous stool» (60%) had about half of all patients in the study. The symptoms testifying complication of disease, such as spastic abdominal pain (80%), flatulence (87%) and anal painfulness (73%) were revealed as well. As a result of treatment in all patients normalization of defecation act frequency, and resolution or significant decrease of other clinical symptoms of constipation are marked. Dynamics of PEGEG parameters, namely electrical activity (Pi/Рs) of every region of GIT before treatment, quotient of various gut regions interrelation, and rhythmicity quotient (Kritm) in general, proved presence of concomitant pathology of the upper parts of GIT, severe dysfunctional disorders. At the same time scores representing electrical activity of the large intestine, remained subnormal both prior and after course of treatment. In no patients drug side effects were not observed.Conclusions. The osmotic laxative polyethylene glycol 4000 has high clinical effect at treatment of constipation in children.